The effect of fatigue on lower-limb biomechanics during single-limb landings: A systematic review - Santamaria, L. J.; Webster, K. E. (Journal of Orthopaedic & Sports Physical Therapy, 2010)
Systematic literature review. OBJECTIVE: To evaluate the quality and outcomes of published research papers on the topic of fatigue-induced biomechanical changes in single-limb landings. BACKGROUND: Lower extremity fatigue causes a number of biomechanical alterations that may increase the risk of knee injury. It has therefore been suggested that fatigue elements be incorporated into injury prevention programs. For this to be successful, protocols that reliably induce fatigue need to be identified and the effect fatigue has on the lower-limb joints needs to be documented. METHODS: A systematic review was conducted to identify published studies that assessed the effect of fatigue on lower-limb biomechanics during single-limb landing tasks. Studies were identified by searching 6 databases, reference lists, and citation tracking. The methodological quality of each paper was assessed, and effect sizes were calculated to allow comparison of results across studies. RESULTS: Eight studies met the inclusion criteria. Numerous methodological differences between the studies made synthesis of data challenging. There was some evidence to show that vertical ground reaction forces and hip and knee joint moments were reduced after fatigue. Kinematic changes were less consistent and require further study. CONCLUSION: The current body of studies showed mixed findings, particularly in relation to landing kinematics after fatigue. Future studies should focus on developing standardized fatigue protocols that include both local and central fatigue effects and monitor progression of fatigue over time. This area of research should be extended to include individuals recovering from musculoskeletal injury or surgery.